Biohydrogen production by dark fermentative bacteria using starchy waste: a review - Ulhiza, Tami Asti; Mohamad Puad, Noor Illi; Azmi, Azlin Suhaida (Kulliyyah of Engineering, International Islamic University Malaysia, 2016)
The need of energy from fossil fuel has become a global issue that is challenging to the humanity due to its high demand. However, fossil fuel is a non renewable form of energy which, in turn, will lead to the energy scarcity. As a matter of fact, researcher has put a strong emphasize to find the alternative source of energy. Biohydrogen produced from the waste has a potential to be an alternative energy for the future. Numerous papers have discussed biohydrogen process technology using several methods such as dark fermentation, photofermentation and integration of both methods. Unfortunately, there is still lack of papers addressing specifically on what is the most suitable bacteria for biohydrogen production. On the other hand, dark fermentative bacterium is a robust bacterium. Dark fermentative bacteria are reported to have capability in consuming sludge and waste to synthesize biohydrogen. Therefore, this paper aims to discuss the correlation between dark fermentative bacteria as an agent, with hydrogen yield. The scope of this paper will focus on the performance and requirement of different species of dark fermentative bacteria using starchy waste as substrate.